EFFECT OF METOPROLOL ON COGNITIVE FUNCTION IN HYPERTENSIVE PATIENTS OF YOUNG TO MIDDLE AGE - S. A. Smakotina; O. A. Trubnikova; O. L. Barbarash (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To evaluate the effect of metoprolol tartrate on blood pressure (BP) and cognitive function in young to middle aged patients with essential hypertension (HT).Material and methods. 40 men (age of 49,0±1,9 y.o.) with HT of I-II stage not taking antihypertensive medication regularly were enrolled into the study. All patients were given metoprolol tartrate (start dose 50-100 mg/d). Variables of 24-h BP monitoring and clinic BP, left ventricular mass index (measured by echocardiography) and characteristics of cognitive function (memory, attention, thinking and neurodynamic) were assessed at the start, after 1 and 6 months of therapy.Results. Good and satisfactory antihypertensive effect was achieved in 75% of hypertensive patients with metoprolol (186,6±13,4mg/d) monotherapy. Metoprolol significantly decreased maximum day-time systolic and diastolic BP, maximum night-time diastolic BP, mean day-time systolic and night-time diastolic BP, time-index, load-index and variability-index for night-time diastolic BP, day-time and night-time pulse BP. Left ventricular mass index reduced significantly (p<0,0001). After 6 months of therapy significant improvement of memory, attention, thinking and neurodynamic was observedConclusion. Metoprolol had beneficial effect on cognitive function in hypertensive patients, which demonstrate its cerebroprotective properties in addition to antihypertensive action. Metoprolol can reduce the risk of dementia in young to middle aged patients with HT.